Behavioral change communication strategy options to improve under five-year children’s nutrition: a scoping review - Mumtaz, Firial Afra Raisa; Sudiarti, Trini (BKM Public Health and Community Medicine, 2024)
Purpose: This study aims to identify some evidence-based strategies as lessons learned for Indonesia to improve behavioral change communication (BCC) nutrition-related strategies in the future of children under five years of age. Methods: A literature review was conducted using two public databases: PUBMED and PLOS ONE, and grey literature, focusing on randomized controlled studies addressing BCC related to children under five years of age nutrition. Results: BCC strategies encompass various topics, mainly focusing on child feeding and enhancing the capacities of delivery actors. These strategies aim to improve knowledge and other aspects of behavior change theory, such as perceived benefits and barriers, cues to action, and self-efficacy. Various media, with different frequencies and intensities, were used, targeting different beneficiaries and involving diverse delivery actors. Conclusion: Evidence-based strategies provide valuable lessons for future BCC implementation related to child nutrition in Indonesia. It is recommended to use multiple media channels, address various beneficiaries, and involve diverse delivery actors to enhance knowledge, attitudes, and self-efficacy in performing recommended behaviors.